2011
DOI: 10.1002/bem.21701
|View full text |Cite
|
Sign up to set email alerts
|

Myotube orientation using strong static magnetic fields

Abstract: In this experiment, we evaluated the effects of strong static magnetic fields (SMF) on the orientation of myotubes formed from a mouse-derived myoblast cell line, C2C12. Myogenic differentiation of C2C12 cells was conducted under exposure to SMF at a magnetic flux density of 0-10 T and a magnetic gradient of 0-41.7 T/m. Exposure to SMF at 10 T led to significant formation of oriented myotubes. Under the high magnetic field gradient and a high value of the product of the magnetic flux density and magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
8
1
1
Order By: Relevance
“…Although additional biomaterial-based approaches have induced similar improvements in muscle function through the codelivery of myogenic bioagents with endothelial cells to enhance vascularization (5.5-fold increase in active stress over blank scaffold) or neural stem cells to promote innervation of muscle constructs (2.0-fold increase in maximum tetanic force over nerve-deficient controls) (44)(45)(46)(47), no bioagents were delivered from the scaffolds in this study. It is possible that the magnetic field directly affected regeneration in the current study, as past studies involving treatment of myoblasts and myotubes with static magnetic fields have demonstrated increased myogenic differentiation and cell alignment (48,49). However, although a slight increase in peak tetanic force was observed with magnetic field application in the current study, results were not significantly different from the untreated controls, perhaps because of the relatively short duration of magnetic field exposure.…”
Section: Markers Of Muscle Regeneration: Centrally Located Nuclei Andcontrasting
confidence: 50%
“…Although additional biomaterial-based approaches have induced similar improvements in muscle function through the codelivery of myogenic bioagents with endothelial cells to enhance vascularization (5.5-fold increase in active stress over blank scaffold) or neural stem cells to promote innervation of muscle constructs (2.0-fold increase in maximum tetanic force over nerve-deficient controls) (44)(45)(46)(47), no bioagents were delivered from the scaffolds in this study. It is possible that the magnetic field directly affected regeneration in the current study, as past studies involving treatment of myoblasts and myotubes with static magnetic fields have demonstrated increased myogenic differentiation and cell alignment (48,49). However, although a slight increase in peak tetanic force was observed with magnetic field application in the current study, results were not significantly different from the untreated controls, perhaps because of the relatively short duration of magnetic field exposure.…”
Section: Markers Of Muscle Regeneration: Centrally Located Nuclei Andcontrasting
confidence: 50%
“…One important issue is the possible direct impact of this magnetic field on MSC differentiation. Indeed, some studies have suggested an influence of static and alternating magnetic fields on the functions of neurons,18 myotubes,19 and stem cells 20. Osteogenesis, adipogenesis and chondrogenesis were thus investigated in the presence and absence of a 0.2‐T magnetic field, and no influence was observed on any of these three differentiation pathways (Figure S2).…”
mentioning
confidence: 99%
“…Sakurai et al demonstrated that the exposure to strong SMF (10 T) led to significant numbers of orientated myotubes in cultures from the mouse-derived myoblast cell line (C2C12). No effect on differentiation was observed when 3 T was applied (13). Furthermore, Kim et al demonstrated that SMF (2 T) in C2C12 myoblast cells inhibits proliferation and may delay cell growth by altering the subcellular localization of gamma complex protein 3 (14).…”
Section: Immunohistochemistry and Fimentioning
confidence: 99%